Performance and Organ Weights of Laying Hens Fed Diets Containing Graded Levels of Sun-dried Cocoa Bean Shell (CBS) - Emiola , I.A.; Ojebiyi, O.O.; Akande, T.O. (International Journal of Poultry Science, 2011)
Response of laying hens fed different levels of cocoa bean shell (CBS) was investigated using eighty 18-weeks old shaver Brown pullets in a six weeks feeding trial. Five rations were formulated by addition of 0, 15, 20, 25 and 30% cocoa bean shell and allocated to five groups of bird (16 birds/group) in a completely randomized design of experiment. Each group was further subdivided into eight replicates of 2 birds per replicate. The control diet was a maize-soybean meal based diet formulated to meet the nutrient requirement of a laying bird with no sun-dried cocoa bean shell (CBS), diets 2, 3, 4 and 5 contained 15, 20, 25 and 30 percent sun-dried cocoa been shell, respectively. Compared with the control diet, average daily feed intake (ADFI), egg production per bird per week as well as percent hen day production (HDP, %) were lower in diet 2 (15% CBS) (P < 0.05). Increasing the level of CBS from 0 to 30% in the diets resulted in linear decreases in ADFI, egg production per week and percent HDP (P < 0.05). Intake of theobromine increased with increasing level of inclusion of cocoa bean shell in the diets. The weights of the spleen, kidney and ovary were similar in birds fed the control diet, diet 2 (15% CBS) and diet 3 (20% CBS) (P > 0.05). However, the weights of the spleen, kidney and ovary were depressed in birds fed diets 4 (25%) and 5 (30%) compared with those that received the control diet (P